Frank Zappa's Legacy: Just Another Hoover? - Watson, Ben (Circuit, 2004)
In "Frank Zappa's Legacy: just another Hoover?", Ben Watson reveals that when Frank Zappa referred to his "oeuvre" towards the end of his life, he pronounced the French word like "Hoover", the world's most famous brand of vacuum cleaner. Watson's essay starts with the proposition that Zappa's oeuvre is indeed a Hoover, a critical manoeuvre appropriate for Zappa's Dadaist disdain for cultural values. Establishment critics currently praise Zappa's "genius" as a composer, but this removes the critical sting of his records. In fact, what made Zappa special was his recognition that both commercial commodification and the heritage industry (concepts of "genius") repress desire and suppress music. In a detour into literary and psychoanalytical theory, Watson's zappological algebra reaches the equation: Stéphane Mallarmé + Wilhelm Reich = Frank Zappa. After an art-historical examination of the Hoover motif in Zappa's oeuvre, Zappa's heritage is assessed today: Project/Object, the Muffin Men, The Simpsons and the improvising trio of Eugene Chadbourne, Jimmy Carl Black and Pat Thomas are singled out for praise.